2014
DOI: 10.1007/s00221-014-3999-5
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of P300 waveform in panic disorder

Abstract: The P300 waveform has been inconsistently linked to the maladaptive information-processing characterized in panic disorder (PD). The purpose of this study was to synthesize previous event-related potential (ERP) findings and determine whether patients with PD have significant abnormalities in the P300 wave compared to controls. We performed a systematic literature search for studies published between 1980 and 2013 that reported P300 measurements in patients with PD and controls. Effect size estimates were comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 47 publications
2
12
0
Order By: Relevance
“…Although there was no significant frontal-greater-than-parietal P3b topography in the right hemisphere in the depression group or anxiety group, decreased parietal P3b and increased frontal P3b were observed for both patient groups. Decreased parietal P3b with regard to depression and anxiety is consistent with previous studies 21 23 24 25 35 36 . Increased frontal P3b in the anxiety group arose from increased PFC activities according to the source analysis results.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Although there was no significant frontal-greater-than-parietal P3b topography in the right hemisphere in the depression group or anxiety group, decreased parietal P3b and increased frontal P3b were observed for both patient groups. Decreased parietal P3b with regard to depression and anxiety is consistent with previous studies 21 23 24 25 35 36 . Increased frontal P3b in the anxiety group arose from increased PFC activities according to the source analysis results.…”
Section: Discussionsupporting
confidence: 92%
“…The results of the previous P300 studies of anxiety disorders have not suggested consistent patterns. Decreased parietal P3b in patients with anxiety disorders has been reported in a few studies 23 24 25 , whereas increased frontal P300 subcomponent has been found to be associated with anxiety disorders in one study 26 . Additionally, few studies have investigated P300 in comorbid patients.…”
mentioning
confidence: 83%
“…So far, the underlying theoretical framework about P300 latency is still not well explained. Delayed P300 latency was found in patients with obvious cognitive impairment, such as schizophrenia [61,62], mild cognitive impairment [63], and Alzheimer's disease [63], but not in panic disorders [64] as well as ASD in this meta-analysis. As the synthetic effect sizes contained a significant level of heterogeneity, we conducted subgroup analysis to investigate the root causes and to test if there was difference between groups in each subgroup.…”
Section: Discussionmentioning
confidence: 95%
“…To our knowledge, no previous study has examined the interaction between error processing and the P300 in relation to individual differences in anxiety. Some previous work has found an increased P300 in anxious individuals (Ischebeck, Endrass, Simon, & Kathmann, 2011;Miltner et al, 2005;Simons, 2010;Wang et al, 2013), while other work has not (Howe, Pinto, & De Luca, 2014;Kıvırcık, Yener, Alptekin, & Aydın, 2003;Sachs et al, 2004). To our knowledge, no previous study has examined the relationship between the P300 elicited by flanker stimuli and anxiety; most studies have focused on the P300 in response to emotional stimuli (e.g., images of spiders in spider phobics).…”
Section: Discussionmentioning
confidence: 98%